Hydrothermal Synthesized Zinc Oxide Nanoparticles With Manganese Doping For Supercapacitor - Kiong, Yuen Yee (Universiti Sains Malaysia, 2022)
Transition metal oxides have drawn appealing attraction as supercapacitor electrode especially zinc oxide (ZnO) due to their good electrochemical activity, environmentally friendly and cheap, but the weak conductivity and low charge-discharge rate capability of pure ZnO remain challenging in electrochemical applications. Herein, facile hydrothermal method was applied to synthesized manganese (Mn) doped ZnO nanoparticles at doping concentration of 3 at% (Zn1-xMnxO, x=0.03). The effect of hydrothermal heat treatment temperature (80, 100, 120, 140, 160, 180 to 200 °C) on physical and electrochemical properties of Zn0.97Mn0.03O nanoparticles was investigated. The structural analysis revealed the success of Mn ions incorporation into ZnO hexagonal wurtzite structure with low impurities content. Major constituent elements in the synthesized nanoparticles were confirmed as Mn, Zn and O by elemental composition characterization. The morphological analysis demonstrated the formation of spherical or hexagonal particles with uniform size in the Zn0.97Mn0.03O synthesized at 160 °C. Electrochemical studies showed that hydrothermal heat treated Zn0.97Mn0.03O nanoparticles at 160 °C have excellent response towards pseudocapacitive nature. Cyclic voltammetry analysis showed that the nanoparticles exhibited significantly improved performance as supercapacitors electrode with excellent specific capacitance of 974.2 F g-1 measured at scan rate of 10 mV s-1 due to the Mn ions help in decreasing the charge transfer resistance. The Zn0.97Mn0.03O electrode shows good redox behaviour in galvanostatic charge-discharge analysis. Such impressive properties lead Zn0.97Mn0.03O nanoparticles to be considered as a promising candidate for supercapacitor applications.